St Ives 1939-64 : Twenty five years of painting, sculpture and pottery. - Lewis, David (London : Tate Gallery, 1985)
Barns-Graham, W. ; Cardew, Michael ; Frost, Terry ; Gabo, Naum ; Haughton, David ; Hayman, Patrick ; Hepworth, Barbara ; Heron, Patrick ; Hilton, Roger ; Jewels, Mary ; Lanyon, Peter ; Law, Bob ; Leach, Bernard ; Leach, Janet ; Mellis, Margaret ; Mitchell, Denis ; Nicholson, Ben ; Pearce, Bryan ; Quick, Kenneth ; Scott, William ; Shoji, Hamada ; Wall, Brian ; Wallis, Alfred ; Wells, John ; Weschke, Karl ; Wood, Christopher ; Wynter, Bryan
St Ives 1939-64 : Twenty five years of painting, sculpture and pottery, The Tate Gallery, London, 13 February - 14 April 1985
boek
Keywords: St Ives